A Comparative Study on Electrical Resistivity and Compressive Strength Properties of Cement Composites Incorporating Conductive Materials - Jong-Gun Park; Dong-Ju Seo; Doo-Yeol Lim; Yu-Jae Lee; Gwang-Hee Heo (Advances in Materials Science and Engineering)
Conductive cement composites have attracted high attention in recent years due to the possibility of achieving multifunctional materials. The usual approach has been to incorporate steel fiber, carbon fiber, graphite, and carbon nanotube/or carbon nanofiber into the cement matrix. In this article, an experimental comparative study was conducted on the electrical resistivity and compressive strength properties of cement composites incorporating carbon fiber (CF) and steel fiber (SF), which are conductive materials. The electrical resistivity of the conductive fiber-reinforced cement composites (FRCCs) was measured using the four-probe method, and compressive strength was conducted based on the KS L ISO 679 and ASTMC109/C109M test methods. Their performance was compared and analyzed with plain cement composites (PCCs). Afterwards, the fracture surfaces of the conductive SFRCCs (steel fiber-reinforced cement composites) and CFRCCs (carbon fiber-reinforced cement composites) were also analyzed using a scanning electron microscope (SEM). The experimental results showed that, in all specimens, the electrical resistivity gradually increased as the curing ages elapsed, while the electrical resistivity decreased significantly as the fiber volume fractions increased. Overall, the addition of SF up to a fiber volume fraction of 1.25% did not significantly affect the electrical resistivity of cement composites. In contrast, however, the electrical resistivity of CF decreased slightly even at a low dosage (i.e., 0.1–0.3%), and thereafter, it was significantly decreased. The percolation threshold of the conductive CFRCC incorporating CF used in this experiment was 0.4%, and this seemed to be the optimal CF dosage that can greatly improve the conductive cement composites while maintaining the maximum performance of compressive strength. In addition, the compressive strength of conductive SFRCC was higher than that of PCC, whereas in the case of conductive CFRCC, it showed a greater tendency to decrease significantly as the fiber volume fractions increased. We expect the results of SEM image analysis to be useful as basic data for establishing microstructure mechanisms of reinforcement fibers in the cement matrix.